PEMBERIAN HAK GUNA BANGUNAN DI ATAS HAK PENGELOLAAN: ALTERNATIF PENYELESAIAN MASALAH TANAH PENSIUNAN TNI-AL DI KAVLING PANGKALAN JATI - Dwi Librianto; Lutfi Djoko Djumeno; Fahrul Fauzi (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
The 26.7-hectare land in the Pangkalan Jati plot has become a polemic for retired Indonesian Navy Army who live on the land. Plans related to the transfer of the Pangkalan Jati plots of land to holders of Development Permits faced several obstacles and tended to stagnate. This research is intended to provide a recommendation for solving the problem with the solution of granting the right of building on land with the right of management. This research is normative legal research, namely legal research whose data comes from library materials or what is usually called secondary data. This research resulted in a policy recommendation that the Ministry of Defense in this case the Navy is a legal subject that can be granted the right of management based on legislation because it is included in the category of Central Government Agencies. The problem of transferring land ownership in the Pangkalan Jati plots currently occupied by retired Indonesian Navy can be resolved by a mechanism for granting land rights over land with the right of management. Where the residents of the Pangkalan Jati plots can be given the right of building because the designation of most of the land is for residence. The right of building can be granted because the residents of the Pangkalan Jati plots who are Indonesian citizens fulfill the criteria as legal subjects holding the right of building. The granting of right of building over land with right of management is carried out with a Land Utilization Agreement between the Ministry of Defense, in this case the Indonesian Navy, and residents of the Pangkalan Jati plots. Residents of Pangkalan Jati plots as the right of building holders will later have rights and obligations that can be enjoyed and implemented. The granting of the right of building over land with right of management is expected to be a solution to the problem of land ownership in the Pangkalan Jati plots so as to provide legal certainty for both parties.